Wireless Machine to Machine Based Mobile Substation Monitoring for District Heating System. (26th June 2014) - Bo, Cheng; Xin, Cheng; Chengwen, Zhang; Ying, Liu; Junliang, Chen
Central heating is a sophisticated process, and many factors influence the heating loading for boilers; without comprehensively monitoring and analysis, it is difficult to find out potential hazards of substation heating supplying electrical equipment. This paper presents a wireless machine to machine based district heating monitoring solution that uses smart mobile devices in a global network. In particular, focusing on the design and implementation for GPRS-based multiserial data transmission terminals to collect the PLC/OPC data in the substation, machine to machine communication network is used to handle the transmission monitoring data from boiler room to master station via GPRS devices and data center that uses different smart mobile devices in a global network, and we also illustrated the mobile substation monitoring scenarios for district heating system. Finally, we give the conclusions and future works.